Groundwater - Freeze, R. Allan; Cherry, John A. (New Jersey : Prentice-Hall, 1979)
This book is designed for use as a text in introductory groundwater courses of the type normally taught in the junior or senior year of undergraduate geology, geological engineering, or civil engineering curricula.
1. Introduction -- 2. Physical properties and principles -- 3. Chemical properties and principles -- 4. Groundwater geology -- 5. Flow nets -- 6. Groundwater and the hydrologic cycle -- 7. Chemical evolution of natural groundwater -- 8. Groundwater resource evaluation.
Includes bibliographical references and index.
Keywords: WATER -- UNDERGROUND